A localized meshless approach using radial basis functions for conjugate heat transfer problems in a heat exchanger. (February 2020) - Wijayanta, Agung Tri; Pranowo,
Highlights: A local radial basis function meshless method is proposed for conjugate heat transfer. The meshless method requires only one set of nodes. Artificial compressibility is added to couple pressure to the continuity equation. Numerical simulation is used to analyze three benchmark problems. The results are in good agreement with the solutions and experimental data. Abstract: An understanding of conjugate heat transfer is important for enhancing the thermal performance of heat transfer devices. This study discusses the numerical solutions of the conjugate natural convective heat transfer problem using a local radial basis function meshless method. The temperature difference is assumed to be small enough to ensure the validity of the Boussinesq approximation. An artificial compressibility method is used to couple pressure to the continuity equation. The meshless method requires only one set of nodes, which are distributed in the spatial domain. The semi-algebraic equations are integrated using the second-order Runge–Kutta method. Three benchmark problems of conjugate natural convection with one vertical wall, conjugate natural convection with centrally vertical partition, and natural convection with a conducting solid in the middle of the square cavity are analyzed. The numerical results are compared with three benchmark solutions and experimental results; it was observed that the experimental and predicted results showed good agreement with each other. This numerical study is to contribute to understanding the knowledge of heat and fluid flow mechanisms for conjugate heat transfer in a heat exchanger acquired through experiments.